'Is it like a beat without a melody?': Rap and revolution in Hamilton. Issue 2 (1st June 2018) - Severs, Jeffrey
Hamilton (2015) celebrates rap as the discursively dense, incandescent language of American revolution, democracy and individuality, but the musical also, in its tragic course, portrays rap's limits, especially when post-revolutionary problems of governance and family life arise. In giving these dual fates to the show's central musical language, creator Lin-Manuel Miranda draws on the history of hip hop in general and gangsta rap in particular, offering an implicit critique of vengeful violence through allusions to the allegedly linked murders of Tupac Shakur and Notorious B.I.G. In its close readings of lyrics, this essay focuses on Alexander and Philip Hamilton and John Laurens and draws connections between these characters' development and Miranda's use of abolitionist and revolutionary history. The essay also explores the show's many allegorical attempts to link positions on the political spectrum with different styles of music, from pop and jazz to the increasingly intricate rhyme schemes of hip hop.